2022
DOI: 10.1111/1467-8551.12693
|View full text |Cite
|
Sign up to set email alerts
|

A Critique of the Agency Theory Viewpoint of Stock Price Crash Risk: The Opacity and Overinvestment Channels

Abstract: This study documents a puzzling historical trend in crash risk for US-listed firms: between 1950 and 2019, the firm-year occurrences of idiosyncratic stock price crashes rose from 5.5% to an astonishing 27%. The vastness of the literature notoriously attributes crashes to agency reasons, i.e. self-interested executives who strategically camouflage bad news via the financial reporting opacity and overinvestment channels. Nonetheless, we document that the opacity-and overinvestment-crash relations are non-signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Especially, our study is related to Andreou et al (2023) who criticize the efficacy of accounting opacity as a channel in explaining crash risk. By contrast, earlier studies (e.g., Hutton et al, 2009;Jin & Myers, 2006) suggest that accounting opacity is an important mechanism in predicting stock price crash risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, our study is related to Andreou et al (2023) who criticize the efficacy of accounting opacity as a channel in explaining crash risk. By contrast, earlier studies (e.g., Hutton et al, 2009;Jin & Myers, 2006) suggest that accounting opacity is an important mechanism in predicting stock price crash risk.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, earlier studies (e.g., Hutton et al, 2009;Jin & Myers, 2006) suggest that accounting opacity is an important mechanism in predicting stock price crash risk. Thus, Andreou et al (2023) suggested more future research to rationalize the puzzling surge in stock price crashes. Responding to Andreou et al (2023),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation